Jenis dan habitat “lalat mata bertangkai” (Diptera: Diopsidae) di bogor - Sopian Sopian; Purnama Hidayat (Jurnal Entomologi Indonesia, 2006)
Stalk eye flies (Diptera: Diopsidae) is an insect family which has unique eye morphology. Their eyes are in the distal end of a long stalk. The information of species and their habitats is still very limited in Indonesia. Therefore, the objectives of this research were studying species diversity, habitat, and distribution areas of stalk eye flies in soroundings in Bogor. The sample sites are classified into three areas; lowland, middle, and upland. The flies ware taken with two methods: net sweeping and direct capture, then parts of the body were measured. The observation of stalk eye flies activity and behavior was done in the morning, midday, and afternoon. The result of observation indicated that stalk eye flies were found almost in all areas, from lowland to upland. On 15 survey locations, stalk eye flies were found in 10 locations with the same habitat. The species are Cyrtodiopsis dalmanni and Teleopsis sp.. C. dalmanni was found in 5 locations, and Teleopsis sp. in 9 locations. The observation result of stalk eye flies activity and behavior indicated that the number of stalk eye flies which captured in three period of time were not obviously different. Result from measuring stalk eye flies bodyparts indicated that the average size of male and female flies was not obviously different, except the male stalk is longer than female. In addition, C. dalmanni stalks are longer than Teleopsis sp. stalks.